Analysis of Factors Affecting Women's Productivity in the Gedogan Traditional Woven Fabric Industry In Pringgasela Village, Pringgasela District, East Lombok Regency - Siti Maolida Yulianti; Wahidin Wahidin; Adhitya Bagus Singandaru (Westscience Press, 2024)
The purpose of this study is to analyze the influence of the number of family dependents, marital status, allocation of working time, wages and length of work. This study uses an explanatory quantitative method with a sample of 68 people with a population of 218 people. The data obtained by distributing questionnaires and sampling in the study used simple random sampling. The results in this study show that partially of the five variables used in this study there is one variable that has a significant influence, namely wages (X4) with a significance of 0.0000 < 0.05 while there are four variables that do not have a significant influence, namely the number of family dependents (X1) with a significance value of 0.5773 > 0.05, marital status (X2) with a significance value of 0.1220 > 0.05, the allocation of working time (X3) with a significance value of 0.2099 > 0.05 and the length of working (X5) with a significance value of 0.9379 > 0.05 did not have a significant effect on labor productivity in the gedogan traditional fabric industry in Pringgasela Village. Meanwhile, simultaneously variable X affects work productivity with a significance value of 0.0000 < 0.05. Meanwhile, the R2 Adjusted R-Square value shows that all independent variables are able to explain the dependent variable by 57% and the remaining 43% are explained by other variables outside this study.